Acute Hepatitis E Virus Infection in Two Geographical Regions of Nigeria (2017)
This study was therefore designed to describe acute HEV infection among antenatal clinic attendees and community dwellers from two geographical regions in Nigeria. Seven hundred and fifty plasma samples were tested for HEV IgM by Enzyme Linked Immunosorbent Assay (ELISA) technique. The tested samples were randomly selected from a pool of 1,115 blood specimens previously collected for viral hepatitis studies among selected populations (pregnant women, 272; Oyo community dwellers, 438; Anambra community dwellers, 405) between September 2012 and August 2013. One (0.4%) pregnant woman in her 3rd trimester had detectable HEV IgM, while community dwellers fromthe two study locations had zero prevalence rates of HEV IgM.Detection of HEV IgM in a pregnant woman, especially in her 3rd trimester, is of clinical and epidemiological significance.The need therefore exists for establishment of a robust HEV surveillance system in Nigeria and especially amidst the pregnant population in a bid to improve maternal and child health.